USE OF IMMUNOMODULATORS IN ACUTE RESPIRATORY INFECTION TREATMENT IN FREQUENTLY ILL CHILDREN - M.I. Ivardava ("Paediatrician" Publishers LLC, 2011)
Respiratory infections, relapses of ear, nose, throat infections, acute and chronic bronchial infections - these are the most common infantile infections. Regardless the wide range of medications, treatment of recurrent ENT and respiratory infections is not always effective especially in the group of frequently ill children. This article contains analysis of the necessity of immunomodulation therapy of recurrent respiratory infections as a part of complex prophylaxis and treatment of infants. Key words: children, acute respiratory infection, polyoxidonium, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 103-107)